Navigating Complexity: Harnessing Technology Integrating m-commerce and Supply Chain Management and Evaluating Shopping behavior for Innovation - Sudhanshu pandiya, Sudhir kumar verma (Journal of Neonatal Surgery, 2025)
The dynamic landscape of mobile commerce (m-commerce) and supply chain management (SCM) presents new complexities, especially when analyzed through consumer shopping behaviors. This study explores the integration of m-commerce with SCM and its influence on shopping innovation across five major cities of Uttar Pradesh—Kanpur, Allahabad, Varanasi, Agra, and Lucknow—over the period 2017–2023. Using the Generalized Autoregressive Conditional Heteroskedasticity (GARCH) model, the research estimates the conditional mean of technological adoption and consumer innovation behaviors. The findings reveal significant volatility and learning patterns in consumer behavior, underpinning strategic insights for firms to foster innovative supply chain models and enhance m-commerce integration.